The Effect of Exchange Rate Volatility on Export Performance : A Sectoral Analysis - Nurul Huda; Michelle Yeoh; Ravi Kumar (Proceeding of The International Conference on Economics and Business, 2024)
Exchange rate volatility significantly impacts export performance, particularly in trade-dependent economies. This paper analyzes sector-specific effects of currency fluctuations in manufacturing, agriculture, and technology exports. The findings highlight strategies for mitigating risks through hedging and government interventions.